Recessive inborn errors of type I IFN immunity in children with COVID-19 pneumonia - Zhang, Qian (2022)
Recessive or dominant inborn errors of type I interferon (IFN) immunity can underlie critical COVID-19 pneumonia in unvaccinated adults. The risk of COVID-19 pneumonia in unvaccinated children, which is much lower than in unvaccinated adults, remains unexplained. In an international cohort of 112 children (<16 yr old) hospitalized for COVID-19 pneumonia, we report 12 children (10.7%) aged 1.5-13 yr with critical (7 children), severe (3), and moderate (2) pneumonia and 4 of the 15 known clinically recessive and biochemically complete inborn errors of type I IFN immunity: X-linked recessive TLR7 deficiency (7 children) and autosomal recessive IFNAR1 (1), STAT2 (1), or TYK2 (3) deficiencies. Fibroblasts deficient for IFNAR1, STAT2, or TYK2 are highly vulnerable to SARS-CoV-2. These 15 deficiencies were not found in 1,224 children and adults with benign SARS-CoV-2 infection without pneumonia (P = 1.2 × 10-11) and with overlapping age, sex, consanguinity, and ethnicity characteristics. Recessive complete deficiencies of type I IFN immunity may underlie ∼10% of hospitalizations for COVID-19 pneumonia in children.